2003
DOI: 10.1038/ni906
|View full text |Cite
|
Sign up to set email alerts
|

Aire regulates negative selection of organ-specific T cells

Abstract: Autoimmune polyendocrinopathy syndrome type 1 is a recessive Mendelian disorder resulting from mutations in a novel gene, AIRE, and is characterized by a spectrum of organ-specific autoimmune diseases. It is not known what tolerance mechanisms are defective as a result of AIRE mutation. By tracing the fate of autoreactive CD4+ T cells with high affinity for a pancreatic antigen in transgenic mice with an Aire mutation, we show here that Aire deficiency causes almost complete failure to delete the organ-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
526
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 703 publications
(551 citation statements)
references
References 50 publications
19
526
0
6
Order By: Relevance
“…An alteration of the delicate balance in both central and peripheral tolerance mechanisms may account for the development of autoimmune disorders. Recent studies have documented the importance of Aire in maintaining central tolerance in vivo [5,25,50]. Investigation of mRNA from mTEC revealed an under-representation of certain transcripts in the absence of Aire, implicating a mechanism for Aire in regulating ectopic expression of tissue-specific genes in the thymus [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alteration of the delicate balance in both central and peripheral tolerance mechanisms may account for the development of autoimmune disorders. Recent studies have documented the importance of Aire in maintaining central tolerance in vivo [5,25,50]. Investigation of mRNA from mTEC revealed an under-representation of certain transcripts in the absence of Aire, implicating a mechanism for Aire in regulating ectopic expression of tissue-specific genes in the thymus [5].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the role of Aire in negative selection was demonstrated [5]. These findings were further supported using TCR transgenic mice expressing hen egg lysozyme (HEL) as a surrogate organ-specific antigen under the control of the rat insulin promoter (RIP) [25]. In the absence of Aire, high-affinity antigen-specific CD4 + T cells failed to be deleted in the thymus, implicating that Aire is involved in negative selection of high-affinity autoreactive T cell clones.…”
mentioning
confidence: 93%
“…This helps to establish immune tolerance toward TSA because thymocytes that respond strongly to antigens in the thymus are normally purged from the repertoire or rendered innocuous [2,3]. In the absence of Aire, T cells responsive to Aire-dependent TSA are not tolerized in the thymus, instead escaping to the periphery where they can precipitate the onset of autoimmunity against a wide array of tissues and organs [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…An alternate explanation is that the loss of Aire might affect more than one form of tolerance [2,8,9]. A controversial, but still unresolved, possibility is that Aire-dependent antigens could be important for the development of regulatory T cells in the thymus, perhaps leading Aire-deficient mice to develop regulatory T cell deficiencies already known to be associated with autoimmunity [4,5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Work using Aire Ϫ/Ϫ mice suggests that Aire upregulates the expression of peripheral tissue-specific genes, including prominent autoantigens such as insulin, in the thymic MECs, a process termed ectopic transcription. In Aire Ϫ/Ϫ mice the presentation of this set of peripheral Ags to developing T cells is disrupted, impairing negative selection and, in a transgenic model, allowing high-affinity autoreactive T cells to mature and migrate to the periphery (6,7). More recently, it was shown that Aire also down-regulates many genes (8,9), and appears to have direct effects on the Ag presentation machinery in the thymic MECs (10).…”
mentioning
confidence: 99%